The Impact of Yoga on Heart Rate Variability: A Systematic Review of Randomized Controlled Trials - Giridharan, Selvaraj; Ansari, Jawaher; Pannerselvam, Hari (International Research Journal of Ayurveda & Yoga, 2024)
Background: Heart rate variability (HRV) serves as an indicator of autonomic nervous system function, reflecting the balance between sympathetic and parasympathetic activities. Elevated HRV is associated with enhanced cardiovascular health and resilience to stress, while reduced HRV correlates with adverse health outcomes, including cardiovascular disease, metabolic disorders, and mental health conditions. Yoga, an ancient mind-body practice, has the potential to enhance HRV by improving autonomic regulation. This review aims to evaluate the impact of yoga on HRV in both healthy individuals and clinical populations. Methods: A systematic search was conducted across the Cochrane Library, PubMed, Scopus, and Web of Science databases for randomized controlled trials (RCTs) published between 2015 and 2024. Eligible studies were required to assess the effects of yoga on HRV in diverse populations. Data extraction focused on the characteristics of the interventions, HRV metrics, and outcomes. The quality of the studies was assessed using the Cochrane Risk of Bias Tool. Results: A total of twenty-three studies were included in this review. Findings indicated that yoga interventions improved HRV in participants with cardiovascular conditions, metabolic syndrome, and chronic pain, as evidenced by increased high-frequency (HF) power and a reduced low-frequency to high-frequency (LF/HF) ratio, which suggest enhanced autonomic function. Results regarding mental health populations were heterogeneous, with some demonstrated improvements in HRV, while data from healthy individuals indicated limited changes in HRV, suggesting that yoga may be particularly beneficial for patients with autonomic dysfunction. The quality of the studies varied, with notable limitations pertaining to blinding and sample size. Conclusion: Yoga may have the potential to improve HRV, particularly among patients with chronic conditions. However, the inconsistent findings observed in mental health and healthy populations underscore the necessity for standardized interventions and further research. This review provides support for the incorporation of yoga as a complementary approach aimed at enhancing autonomic function and overall well-being.